Principles Established in Rhode Island - Harkness, R. E. E. (Church history, 1936)
Roger Williams is justly famous in history as the Pioneer Statesman of Religious Liberty. He can never be robbed of this distinction and honor. But it is not the only cause for which he should be famous. According to the well known story, arriving in Massachusetts Bay Colony on February 5, 1631, he declined an invitation to become minister of the Boston Church because it was constituted of “an unseparated people,” still holding fellowship with the Church of England, and because the civil magistrates of the Bay punished for breaches of the First Table, that is exerted authority in religious affairs. After years of controversy with the authorities of the Bay, sentence of banishment was passed upon him in October, 1635, and in January, 1636, he was forced to leave its jurisdiction. Reaching the Narragansett country, he established the Providence Community and later Rhode Island Colony.